Coordination Polymer Flexibility Leads to Polymorphism and Enables a Crystalline Solid–Vapour Reaction: A Multi‐technique Mechanistic Study. Issue 24 (11th May 2015) - Vitórica‐Yrezábal, Iñigo J.; Libri, Stefano; Loader, Jason R.; Mínguez Espallargas, Guillermo; Hippler, Michael; Fletcher, Ashleigh J.; Thompson, Stephen P.; Warren, John E.; Musumeci, Daniele; Ward, Michael D.; Brammer, Lee
Abstract Despite an absence of conventional porosity, the 1D coordination polymer [Ag4(O2C(CF2)2CF3)4(TMP)3] (1; TMP=tetramethylpyrazine) can absorb small alcohols from the vapour phase, which insert into AgO bonds to yield coordination polymers [Ag4(O2C(CF2)2CF3)4(TMP)3(ROH)2] (1‐ROH; R=Me, Et, iPr). The reactions are reversible single‐crystal‐to‐single‐crystal transformations. Vapour‐solid equilibria have been examined by gas‐phase IR spectroscopy (K=5.68(9)×10−5 (MeOH), 9.5(3)×10−6 (EtOH), 6.14(5)×10−5 (iPrOH) at 295 K, 1 bar). Thermal analyses (TGA, DSC) have enabled quantitative comparison of two‐step reactions 1‐ROH→1→2, in which 2 is the 2D coordination polymer [Ag4(O2C(CF2)2CF3)4(TMP)2] formed by loss of TMP ligands exclusively from singly‐bridging sites. Four polymorphic forms of 1 (1‐ALT, 1‐AHT, 1‐BLT and 1‐BHT; HT=high temperature, LT=low temperature) have been identified crystallographically. In situ powder X‐ray diffraction (PXRD) studies of the 1‐ROH→1→2 transformations indicate the role of the HT polymorphs in these reactions. The structural relationship between polymorphs, involving changes in conformation of perfluoroalkyl chains and a change in orientation of entire polymers (A versus B forms), suggests a mechanism for the observed reactions and a pathway for guest transport within the fluorous layers. Consistent with this pathway, optical microscopy and AFM studies on single crystals of 1‐MeOH/1‐AHT show that cracks parallel to the layers of interdigitated perfluoroalkyl chains develop during the MeOH release/uptake process.